Rút gọn biểu thức A=(1 trên x mũ 2 -x + 1 trên x-1) chia x+1 trên x mũ 2 – 2x+1 07/08/2021 Bởi Anna Rút gọn biểu thức A=(1 trên x mũ 2 -x + 1 trên x-1) chia x+1 trên x mũ 2 – 2x+1
Đáp án: $A=\dfrac{x-1}{x}$ Giải thích các bước giải: $A=\left ( \dfrac{1}{x^2-x}+\dfrac{1}{x-1} \right ):\dfrac{x+1}{x^2-2x+1}\\=\left ( \dfrac{1}{x(x-1)}+\dfrac{1}{x-1} \right ):\dfrac{x+1}{(x-1)^2}\\=\left ( \dfrac{1}{x(x-1)}+\dfrac{x}{x(x-1)} \right ):\dfrac{x+1}{(x-1)^2}\\=\dfrac{1+x}{x(x-1)}.\dfrac{(x-1)^2}{x+1}\\=\dfrac{x-1}{x}$ Bình luận
A=(1/x^2−x+1/x−1) : x+1/x^2−2x+1 =(1/x(x−1)+1/x−1) : x+1 (x−1)^2 =[1/x(x−1)+x/x(x−1)]:x+1/(x−1)^2 =x+1/x(x−1) . (x−1)^2/x+1 =x−1/x Bình luận
Đáp án:
$A=\dfrac{x-1}{x}$
Giải thích các bước giải:
$A=\left ( \dfrac{1}{x^2-x}+\dfrac{1}{x-1} \right ):\dfrac{x+1}{x^2-2x+1}\\
=\left ( \dfrac{1}{x(x-1)}+\dfrac{1}{x-1} \right ):\dfrac{x+1}{(x-1)^2}\\
=\left ( \dfrac{1}{x(x-1)}+\dfrac{x}{x(x-1)} \right ):\dfrac{x+1}{(x-1)^2}\\
=\dfrac{1+x}{x(x-1)}.\dfrac{(x-1)^2}{x+1}\\
=\dfrac{x-1}{x}$
A=(1/x^2−x+1/x−1) : x+1/x^2−2x+1
=(1/x(x−1)+1/x−1) : x+1 (x−1)^2
=[1/x(x−1)+x/x(x−1)]:x+1/(x−1)^2
=x+1/x(x−1) . (x−1)^2/x+1
=x−1/x